Model Agen untuk Peramalan Permintaan Retailer menggunakan Metode Double Exponential Smoothing (Studi Kasus: Distributor Toko Gamis di Batam) - Purnamasari, Dwi Amalia; N, Azhari S (Fakultas Teknik Universitas Maritim Raja Ali Haji, 2017)
Forecasting is an attempt to predict what happens in the future, while forecasting demand is an effort that is expected to be realized for a certain period in the future. Distributors difficult forecasting product demand needs of the estimated number of the retailer, the Distributor does not have given an overview of the extent of the need for the required product request is recorded. Therefore, the need for forecasting system that is capable of working on the need for the number of requests the retailer so that for information between the two in order to give the necessary information. The way to resolve problems that occur in this research is to predict demand for the retailers needs by using the method of Double Exponential Smoothing (DES) Holt by considering certain factors. The conclusion of this research that a demand forecasting using DES holt obtained from the accuracy in identifying data, where the data to be continuously experience the trend up or down. Results of the research by using DES Holt method on both retailers have a value different of Î±(alpha), Î³ (gamma) and the smallest value of MSE. At retailer 1 produces a value Î± (alpha) = 0.9, the Î³(gamma) = 0.1, while the retailer 2 produces a value Î± (alpha) = 0.9, Î³ (gamma) = 0.2.